Draft Genome Sequence of an International Clonal Lineage 1 Acinetobacter baumannii Strain from Argentina - Vilacoba, Elisabet (2014)
In the last few years Acinetobacter baumannii has emerged worldwide as an important nosocomial pathogen in medical institutions. Here, we present the draft genome sequence of the international clonal lineage 1 (ICL1) A. baumannii strain A144 that was isolated in a hospital in Buenos Aires City in the year 1997. The strain is susceptible to carbapenems and resistant to trimethoprim and gentamicin.